Mapeamento tecnológico da geração de energia eólica offshore - Barreto, Fernanda de Melo (2019)
Wind energy has been in use since the end of the 19th century. In Denmark, for example, there was the great development of wind power from the manufacture of the first turbines by small agricultural equipment companies. Around 1980, countries such as Germany and the USA through incentive policies, triggered investments with diverse stimuli in R&D. In addition to being a clean alternative, wind power is capable of producing electricity at competitive prices relative to traditional sources of energy. The year 2016 was marked by the cost reduction of the offshore wind energy, in some circumstances, this source becomes less expensive than onshore. Brazil does not yet have offshore wind power plants and there are still few studies in this area. Thus, the objective of this study was to map the existing technologies and technological trends of turbines for offshore wind energy, exploring different rotor technologies and the structure of an offshore wind turbine. The research was carried out in two stages: the theoretical basis, followed by a patent analysis, enabling a technological mapping of the technologies. The patent base Derwent Innovations Index (DII) was used and analyzed with a quantitative and qualitative approach to patents from 1998 to 2018. It is concluded that offshore wind turbines have almost twice the power than onshore turbines, the blades are reinforced with glass fiber and the most commonly used foundation is the monopile. In the future, turbines tend to increase further in power and size, it is expected that the materials used in the blades will feature low density, high strength and can be recycled, and the towers and foundations are in a hybrid trend of materials and model. In addition, there is a trend in the development of technologies for turbines to be implemented in deeper water.